STRUKTUR KEPEMILIKAN, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG PERUSAHAAN PEMANUFAKTURAN DI BURSA EFEK INDONESIA - Syadeli, Moh. (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract: This study intends to find out the impact of the ownership structure, profitability, and firm size to the leverage of the firm simultaneously.Â Moreover, this research is to examine impact of the ownership structure, profitability, and firm size on the leverage of the firm partially, and which is the dominant ones.Â Samples used in this research are selected using purposive sampling from manufactured public companies listed at Bursa Efek Indonesia (BEI) from 2008-2010. Method of this study was multiple regression analysis models. The result shows all the independent variables (ownership structure, profitability, and firm size) have significant influence on leverage of the company simultaneously. Meanwhile, profitability (ROI) has negative significant influence on leverage of the company, however size of the firm has positive significant influence on it. Whereas, ROI (return on investment) is a dominant factor influence on the leverage of the firm. Keywords: ownership structure, profitability, firm size, debt policy.